Is Arabica Coffee Farming Financially Feasible? - Nangameka, Yohanes; Puryantoro, Puryantoro; Iftitah Anugerah Yekti, Gema; Al Yazid, Wahid (Publisher Cv. Inara, 2023)
The objectives in this study are to determine the benefits of arabica coffee farming in Jampit Village, Ijen District and to analyze the feasibility of arabica coffee farming in Jampit Village, Ijen District, Bondowoso Regency. The research method used is descriptive and quantitative methods. Descriptive method is a method for analyzing data by describing the data that has been collected as it is without intending to make general conclusions or generalizations. The quantitative method is a type of research whose specifications are systematic, planned and clearly structured from the start as far as the research design. The results showed that the profit of arabica coffee farming based on analysis using NPV is Rp. 30,621,659 over a period of 4 years, it was said to be profitable and based on NPV analysis obtained at an interest rate of 6% produced a positive NPV value of Rp. 19,613,917 .09 is greater than zero (NPV > 0) then it is said to be feasible. Arabica coffee farming in Jampit Village, Ijen District, Bondowoso Regency is feasible based on the analysis of R/C Ratio, Net B/C and IRR. Based on the R/C Ratio analysis, the result is 1.82 which is greater than 1, so it is efficient. Based on the Net B/C analysis, the result is 0.82 which is less than 1, which means it is not feasible, and based on the IRR analysis, it produces an IRR value of 58.62. % is greater than 6% (interest rate) then it is stated to be feasible because it meets the investment criteria.